Ranolazine reduces repolarization heterogeneity in symptomatic patients with diabetes and non–flow‐limiting coronary artery stenosis. Issue 1 (27th June 2017) - Evaristo, Ederson; Stocco, Fernando G.; Shah, Nishant R.; Cheezum, Michael K.; Hainer, Jon; Foster, Courtney; Nearing, Bruce D.; Di Carli, Marcelo; Verrier, Richard L.
Abstract : Background: Experimental evidence suggests that ranolazine decreases susceptibility to ischemia‐induced arrhythmias independent of effects on coronary artery blood flow. Objective: In symptomatic diabetic patients with non–flow‐limiting coronary artery stenosis with diffuse atherosclerosis and/or microvascular dysfunction, we explored whether ranolazine reduces T‐wave heterogeneity (TWH), an electrocardiographic (ECG) marker of arrhythmogenic repolarization abnormalities shown to predict sudden cardiac death. Methods: We studied all 16 patients with analyzable ECG recordings during rest and exercise tolerance testing before and after 4 weeks of ranolazine in the double‐blind, crossover, placebo‐controlled RAND‐CFR trial (NCT01754259). TWH was quantified without knowledge of treatment assignment by second central moment analysis, which assesses the interlead splay of T waves in precordial leads about a mean waveform. Myocardial blood flow (MBF) was measured by positron emission tomography. Results: At baseline, prior to randomization, TWH during rest was 54 ± 7 μV and was not altered following placebo (47 ± 6 μV, p = .47) but was reduced by 28% (to 39 ± 5 μV, p = .002) after ranolazine. Ranolazine did not increase MBF at rest. Exercise increased TWH after placebo by 49% (to 70 ± 8 μV, p = .03). Ranolazine did not reduce TWH during exercise (to 75 ± 16 μV), and there were no differences among the groups ( p = .95, ANOVA). TWH was not correlated with MBF at rest before ( r 2 = .07, p = .36) or after ranolazine ( r 2 = .23, p = .06). Conclusions: In symptomatic diabetic patients with non‐flow‐limiting coronary artery stenosis with diffuse atherosclerosis and/or microvascular dysfunction, ranolazine reduced TWH at rest but not during exercise. Reduction in repolarization abnormalities appears to be independent of alterations in MBF.